Absorption of infrared radiation by carbon monoxide at elevated temperatures and pressures: Part B. Total emissivity charts and correlations. (October 2017) - Alberti, Michael; Weber, Roman; Mancini, Marco
Abstract: The line-by-line procedure developed in the associated paper (Part A ) has been used to generate the total emissivity chart for pure CO and CO − N 2 / air mixtures at 1 bar total pressure, in the 300 to 3000 K temperature and 0.01 to 3000 bar cm pressure path length range. Methods of scaling the emissivity to pressures different to 1 bar, in the range 0.1 to 40 bar, are provided through pressure correction graphs and EXCEL interpolator (Supplementary Material). The interpolated emissivities are within ± 2% margin from the line-by-line calculated values. The newly developed emissivity graphs are substantially more accurate than the existing Ulrich (1936) & Hottel (1954) and Abu-Romia & Tien (1966) charts.